The Kurdish National Movement - Othman Ali (International Institute of Islamic Thought, 2008)
A native of Iraq,Wadie Jwaideh founded the Islamic and Near Eastern studies program at Indiana University (Bloomington) in the early 1960s and oversawits rise to national and international recognition until his retirement in the mid-eighties. Under his leadership, Indiana University became an internationally renowned center for the study of Islam and the Middle East. His counsel was often sought by many, including heads of state. Moreover, his encyclopedic knowledge of Arabic, Islamic history, and culture was unmatched. In 2004, his students and friends founded the Jwaideh Memorial Lecture. This book chronologically follows the developments of the Kurdish question from the suppression of semi-autonomous Kurdish emirates (principalities) in the Ottoman Empire during the nineteenth century, through the First World War and the Kurdish rebellions of the 1930s and 1940s and the establishment and fall of the short-lived Kurdish Republic of Mahabad. Although his main concerns revolve around the Kurdish nationalist movement’s relative strength and relations to international politics in the Middle East, he follows a comprehensive analytical approach and gives the role of economic, religious, and psychological factors considerable weight. In his foreword, the well-known Kurdologist Martin van Bruinessen writes that “many scholars have recognized its importance not only as a study of the earlier phases of Kurdish nationalism, but also as a framework for understanding later developments.” During the preparation of this study, which was originally a Ph.D. dissertation for Syracuse University in 1960, Jwaideh states of the Kurds: “Their behavior is one of the important factors in the future stability and security not only of the Kurdish-inhabited countries, but of the entireMiddle East” (p. xiv). I strongly agree with Bruinessen that this statement is more relevant today than ever; current events in Iraq only serve to bear out how far-sighted Jwaideh was about the Kurds’ role in the modern Middle East ...